Three new species of the fern genus Pteridrys (Tectariaceae) from Vietnam - Zhang, Liang; Lu, Ngan Thi; Zhou, Xin-Mao; Zhang, Li-Bing (Phytotaxa, 2017)
The fern genus Pteridrys is characterized by having free veins and a tooth on each sinus between two pinna or pinnule lobes. This genus is currently known from nine to ten species. Here we add three new species of Pteridrys from northern Vietnam found in an expedition in 2013.